Histopathological analysis of tilapia gills (Oreochromis niloticus Linnaeus, 1758) exposed to sugarcane vinasse - Correia, J. E. [UNESP]; Christofoletti, C. A. [UNESP]; Marcato, A. C.C. [UNESP]; Marinho, J. F.U. [UNESP]; Fontanetti, C. S. [UNESP] (Elsevier, 2017)
Sugarcane vinasse is one of the main residues generated by the transformation of cane into ethanol. Because of the high organic content (COD), high biochemical oxygen demand (BOD), low pH, the large amount that this residue is generated (15 l for every liter of ethanol produced) and their use as fertilizer on the sugarcane crop, this residue is potentially polluting to the soil ecossystem and by percolation to water ecossystem too. Thus, this study aimed to assess the toxicity of vinasse by analyzing Oreochromis niloticus gills exposed to different dilutions (1%, 2.5%, 5% and 10%) in two bioassays. The gills were collected, fixed and analyzed using ultra morphological, histological, and histochemical techniques. After exposure to the vinasse, a statistically significant reduction of the ridges present on the surface of pavimentous cells was observed in one of the bioassays; such structures are responsible for mucus retention, which helps to protect the tissue. In addition, an intumescence of the cells was observed in the treatments with vinasse as well as an increase in the amount of chloridric cells. Some striking tissue changes detected in the treatments were epithelial detachment and loss of integrity of secondary lamellae, causing their rupture and consequent hemorrhage. In the first bioassay, the amount of these changes was statistically significant at the 5% dilution, and the focus of hemorrhage was significant at all dilution ratios. In the second bioassay, the epithelial disorganization was statistically significant only at the 2.5% dilution of vinasse. Moreover, for both bioassays performed, a significant increase in mucous cells was observed when compared with the control. Our results demonstrate the toxic action of sugarcane vinasse, which caused histopathological changes in the exposed animals at all four dilution tested. This highlights the need for caution in the disposal of sugarcane vinasse on the soil, especially due to its capacity for being leached or percolated into water resources, which could seriously damage aquatic fauna.
Keywords: Aquatic toxicity; Histochemical; Histology; Stillage; Ultra-morphology